The effect of profitability, liquidity, and capital structure toward stock returns: A study on plantation companies listed in IDX - Yoel Silver; Christina Tri Setyorini; Umi Pratiwi (Journal of Contemporary Accounting, 2023)
This study aims to analyze the effect of profitability, liquidity, and capital structure on stock returns. This study uses signaling theory as a research basis. This study uses a quantitative approach with a regression method, whose population data are plantation sub-sector companies listed on the IDX for the 2016-2021 period. The sample selection was carried out using purposive sampling and obtained as many as 90 samples from 15 companies. Based on the results using EViews 12, its indicate that profitability had a significant positive effect on stock return, liquidity did not have a significant effect on stock return, and capital structure did not have a significant effect on stock return. The implication of this study is that investors must pay close attention to the profitability ratio, as a high profitability ratio correlates to a higher rate of return. In the meantime, businesses must evaluate their use of capital in order to avoid going bankrupt, as well as assess their debt. The originality of this research is that it was undertaken in the plantation sub-sector, where few previous researchers had focused.